Pembuatan Sarana Air Bersih di Kampung Pasir Tugu Desa Ciasmara - Herlina; Ismail Mustaqim; Wiwi Uswatiyah; Ery Subaeri; Ajun; Kholipah Maulidina; Regina Ananda Putri; Fitra Maulidina; Fitri Irma Amalia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study evaluates the establishment of clean water facilities in Pasir Tugu Village, Ciasmara, focusing on the planning, implementation, and impact of the clean water supply system. This community service initiative is driven by the lack of clean water facilities in every home to meet daily needs. The objectives of this service are to identify the needs and challenges in providing clean water, evaluate the implementation process of the clean water system, and assess the system's impact on water quality. The methods employed include initial meetings with residents, community participation, needs surveys, water quality testing, and impact evaluation. The results indicate a significant improvement in water quality and community health.